Characterization of Avian Influenza Virus H10–H12 Subtypes Isolated from Wild Birds in Shanghai, China from 2016 to 2019 - Ling Tang; Wangjun Tang; Le Ming; Jianming Gu; Kai Qian; Xiaofang Li; Tianhou Wang; Guimei He (Viruses, 2020)
H10, H11 and H12 (H10–H12) subtypes of the avian influenza virus (AIV) are associated with waterfowl. Although these subtypes of AIV are infrequently detected in nature, they can undergo reassortment with other AIV subtypes. Few H10–H12 subtypes of AIV have been isolated from wild birds in China. In this study, 12 AIV isolates of H10–H12 subtypes were identified via routine surveillance of wild birds in Shanghai, China from 2016 to 2019, including two H10, three H11 and seven H12 isolates. Sequence and phylogenetic analyses revealed that the genomic segments of the 12 isolates are highly diverse. These 12 isolates are closely related to those in the Eurasian lineage and share a high degree of sequence identity with those from wild birds and domestic ducks in countries in the East Asian–Australasian Flyway, including Japan, Korea, Bangladesh, Vietnam and China. However, parts of the genomic segments of two H12N2 isolates (NH112319-H12N2 and NH101807-H12N2) belong to the North American lineage, suggesting intercontinental reassortment among H12 AIVs in Eurasia and North American. To better understand the ecological and phylodynamic features of H10–H12 subtypes in wild birds, a large-scale surveillance of AIVs in wild birds is warranted.